Central Blood Pressure Responses to Dietary Sodium and Potassium Interventions. (27th January 2018) - Xing, Xiaolong; Liu, Fangchao; Yang, Xueli; Huang, Chen; Zhang, Dingding; Chen, Shufeng; Chen, Jichun; Li, Jianxin; Liu, Zhendong; Lu, Fanghong; Gu, Dongfeng; Huang, Jianfeng
Abstract: BACKGROUND: To explore how central hemodynamics respond to dietary sodium and potassium interventions, and whether the responses are associated with metabolic traits. METHODS: We conducted a dietary intervention study including a 7-day low-sodium (51.3 mmol sodium/day) intervention, a 7-day high-sodium (307.8 mmol sodium/day) intervention, and a 7-day high-sodium with potassium supplementation (60.0 mmol potassium/day) intervention among 99 northern Chinese subjects aged 18–60 years. Five metabolic traits included abdominal obesity, high triglycerides, low HDL cholesterol, raised blood pressure (BP), and high glucose. Central hemodynamics were measured at baseline and during each intervention. RESULTS: Central systolic BP (SBP), diastolic BP (DBP), pulse pressure (PP), and augmentation index (AIx@75) significantly decreased during low-sodium intervention, increased during high-sodium intervention, and then decreased during potassium supplementation. We observed potential linear trends toward significance of central SBP and PP responses to low-sodium intervention, and significant linear trends of responses to high-sodium intervention as the number of metabolic traits grows. For example, among participants with 0 or 1, 2 or 3, and 4 or 5 metabolic traits, central SBP responses to high-sodium intervention were 8.8 [95% confidence interval (5.8, 11.8)], 9.3 (7.1, 11.6), and 14.0 (11.6, 16.3) mmHg, respectively ( P for trend = 0.009). Significant linear trends of central SBP and DBP responses to potassium supplementation were also observed. CONCLUSIONS: Central BP and AIx@75 were lowered by sodium reduction and potassium supplementation, and elevated by sodium-loading. The responses of central BP were pronounced among individuals with metabolic traits clustering. CLINICAL TRIALS REGISTRATION: Trial Number NCT00721721 (The current study is registered on ClinicalTrials.gov; https://clinicaltrials.gov ).